Pengaruh Beban Kerja, Komunikasi Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan Pada Kantor Kecamatan Yang Ada Di Kota Mataram - Nurhidayah; Lalu Mimbar; Surahman Hidayat (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to determine and analyze the significant partial influence of workload, work communication and work stress on employee satisfaction at the sub-district office in Mataram City. The population in this study was all 157 sub-district office employees in Mataram City. This research uses the Slovin technique because the population is large, so the sample in this research was narrowed so that a sample of 113 respondents at the sub-district office in Mataram City was obtained. The data analysis method used in this research is Multiple Linear Regression. The research results show that: (1) Workload has a partially significant effect on job satisfaction. (2) Communication has a partially significant effect on job satisfaction. (3) Job stress does not have a partially significant effect on job satisfaction.